Poverty and the welfare costs of risk associated with globalization - Ethan Ligon (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
`Globalization' implies change, and uncertainty over future change may affect household welfare. We use data on Lorenz curves over the last fifty years for a sample of 53 (mostly developing) countries. Treating each country-quintile-year as an observation, we first account for variation in consumption expenditures, finding that global shocks are of less importance than country-level shocks in explaining variation in country-quintile consumption growth. While poorer households experience more rapid consumption growth than do wealthier households, they also bear much more risk. However, we find no evidence that this greater risk is related to globalization. – globalization ; risk ; growth ; inequality ; shocks ; consumption
Keywords: F02; O47; E21; 330; Armut; Globalisierung; Einkommensverteilung; Lorenz-Kurve; Entwicklungsländer